Lake effect : a novel - Sweeney, Cynthia D'Aprix (Ecco, an imprint of HarperCollins Publishers, 2026)
"From the New York Times bestselling author of The Nest and Good Company comes a wry and tender portrait of two families forever changed by one love-struck decision that will reverberate for decades. It's 1977 and an air of restlessness has settled on the residents of Cambridge Road in Rochester, New York, a place long fueled by the booming fortunes of Kodak and Xerox and, for some, the mores of the Catholic church. When Nina Larkin is given a copy of The Joy of Sex by her newly divorced friend, she can no longer dismiss the nearly nonexistent intimacy of her marriage. Just as her oldest child, Clara, is falling in love for the first time, Nina finds herself longing for the forbidden: a midlife awakening. An intoxicating fling with a prominent neighbor brings Nina a freedom she never thought possible-but also risks the reputations of both families and unravels Clara's world, just as she stands on the threshold of adulthood. Years later, Clara, now a successful food stylist in New York City, has never been able to move past the long-ago scandal. Drawn back home by the pull of a family wedding and wrestling with her own demons, she makes a pivotal decision that turns her life upside down. Written with Cynthia D'Aprix Sweeney's signature humor and insight, Lake Effect is a wise and probing look at love and desire, mothers and daughters, loss and grief, and what we owe the people we love most"-- Provided by publisher.